Advanced financial accounting (McGraw-Hill Irwin, 2008)
The seventh edition of Advanced Financial Accounting is a comprehensive and highly illustrated presentation of the accounting and reporting principles used in a variety of business entities. The complete presentations of worksheets, schedules, and financial statements allow students to see the development of each new topic. The book's building block approach introduces concepts with simple examples and then gradually introduces complexity, allowing students to easily keep pace with the material